2005
DOI: 10.1002/jsfa.2119
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain fatty acid supplemented infant formula does not influence calcium and magnesium bioavailability in weanling rats

Abstract: The influence of infant formula supplementation with long-chain-polyunsaturated fatty acids (LCPUFA) on calcium and magnesium bioavailability was assessed in rats. Two test diets containing a plain, unsupplemented (PF) or supplemented (SF) infant formula as the fat source and a control diet (C) were administered to weaning rats and food intake and body weight gain were monitored for 28 days. In order to assess calcium and magnesium bioavailability, during the last week faeces and urine were collected and appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Likewise, lipids impact the absorbability of Mg 2+ , whereby the lipid composition is suggested to be the influencing factor. Rat studies showed that a replacement of Medium Chain Triglycerides (MCT) for Long Chain Triglycerides (LCT) increased Mg 2+ absorption [ 65 , 66 ], possibly due to more soluble Mg 2+ soaps of saturated fatty acids compared to insoluble Mg 2+ salts formed with unsaturated fatty acids [ 67 ]. Conversely, studies on the influence of absolute fat mass on Mg 2+ absorption have not produced consistent results ([ 68 - 70 ], reviewed in [ 64 ]).…”
Section: Data On Intestinal Mg2+ Absorptionmentioning
confidence: 99%
“…Likewise, lipids impact the absorbability of Mg 2+ , whereby the lipid composition is suggested to be the influencing factor. Rat studies showed that a replacement of Medium Chain Triglycerides (MCT) for Long Chain Triglycerides (LCT) increased Mg 2+ absorption [ 65 , 66 ], possibly due to more soluble Mg 2+ soaps of saturated fatty acids compared to insoluble Mg 2+ salts formed with unsaturated fatty acids [ 67 ]. Conversely, studies on the influence of absolute fat mass on Mg 2+ absorption have not produced consistent results ([ 68 - 70 ], reviewed in [ 64 ]).…”
Section: Data On Intestinal Mg2+ Absorptionmentioning
confidence: 99%
“…7 On the other hand, LCPUFA do not affect Ca and Mg bioavailability when included in infant formulas. 8 In the food industry the composition and structure of human milk oligosaccharides have not been reproduced and therefore they are not commercially available. This is why oligosaccharides of animal and vegetable origin (chiefly fructooligosaccharides and galactooligosaccharides, also known as prebiotics) are normally used in infant feeding to obtain similar effects to those described for human milk oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Mg supplementation combined with vitamin E, which effectively scavenges the peroxyl radical in cell membranes to inhibit lipid peroxidation, has been hypothesized to exert a synergistic effect on glycemic control [ 133 ]. Lipids impact the absorbability of Mg, whereby the lipid composition is suggested to be the influencing factor [ 134 ]. Specifically, the regular consumption of dairy products and milk formulas are foods of high nutritional value that provide high amounts of Ca, Mg, P, and vitamin D, which are chief factors in bone health [ 135 ].…”
Section: Discussionmentioning
confidence: 99%